'MONUMEN KREWENG' 3D ANIMATION VIDEO AS A VISUAL BRANDING STRATEGY FOR JURON TOURIST VILLAGE - Marwanto, Aries Budi; Afrianto, Damar Tri; Dwi Atmaja, Nur Rahmat Ardi Chandra (Capture : Jurnal Seni Media Rekam, 2021)
The development of tourist destinations in this digital era focuses on using technology to develop successful tourism recovery during the pandemic era. We use this principle to develop a tourism strategy using 3D animated videos to introduce Juron Village as a tourist village. Specifically, this study analyzes the visual strategy of a 3D animation video entitled "Monumen Kreweng" using Marty Neumeier's visual branding analysis. The findings provide insight into the animated video's visual branding strategies, including differentiation, collaboration, innovation, validation, and cultivation. The differentiation is found in the work of the Kreweng monument as the focal point of attention and local wisdom, followed by validation through the use of social media platforms to solicit consumer feedback on visual branding. Finally, the cultivation concept encourages various stakeholders to participate in realizing Juron Village's tourism branding.